Empowerment of Community Health Center Providers about Screening Multidimensional Frailty - Tallutondok, Eva Berthy; Siswadi, Yakobus; Sitanggang, Yenni Ferawati; Octaria, Martha; Sihombing, Riama Marlyn; Iradewi, Iradewi (Universitas Malahayati Lampung, 2025)
ABSTRACT The increasing number of elderly people in Indonesia underscores the need for knowledge about the vulnerabilitiesand health issues affecting the elderly population. Furthermore, the lack of skills among carers and the healthcaresystem to provide adequate, preventive, and dignified care makes it essential to initiate action. The main goal is to disseminate the research results and introduce the multidimensional frailty assessment questionnaire to healthcare providers in Community Health Centres. The procedures commenced through collaboration with the Dinas Kesehatan Kota Bandung. The participatory action technique was employed to incorporate research findings into community service activity through joint planning. Two phases of the program: workshop and follow-up. Discussion, demonstration, and re-demonstration within peer groups were utilized for workshops, with site visits to obtain feedback from participants randomly. 12 Community Health Centres participated in this community service initiative. Six sites were designated for research, while six other sites are situated near Bandung Kulon. Each Community Health Centre was invited to send two representatives, including the principal and the individual responsible for geriatric polyclinics (n=24). This study utilized the Wilcoxon Signed-Rank Test and Interpretative Phenomenological Analysis. The results showed that the workshop effectively improved the knowledge and skills of most healthcare workers, with a p-value of 0.001 (<0.05). Furthermore, the follow-up phase involved exploring healthcare providers’ perspectives on the use of frailty screening for elderly patients at Community Health Centres, which yielded three main themes: Theme 1, Tools and Instruments Used in Screening; Theme 2, Challenges in the Screening Process; and Theme 3, Optimization and Adaptation of the Screening Process. This workshop demonstrated an improvement in critical thinking, problem-solving, and other cognitive skills among healthcare workers. Additionally, the perspectives of primary healthcare providers regarding the implementation of frailty screening for elderly patients at Community Health Centres emphasized the importance of multidimensional frailty assessment for elderly visitors to the centres. Keywords: Community Service Program, Knowledge, Practice, Workshop